Bibliometrik Sistem Informasi Akuntasi pada UMKM (Analisis Co-Occurance Basis Data Google Schoolar) - Nurfadila, Septiyana (STIE PENA, 2023)
One of the most important knowledge resources, especially for MSMEs, is the ability to manage finances. This study aims to be able to produce a bibliometric analysis of accounting system publication trends in MSMEs. Bibliometric analysis studies on accounting systems in MSMEs are still very limited by researchers. The method used to map the accounting system is using Systematic Mapping Study (SMS) mapping with Bibliometric Analysis. Data sources sourced from the Google Scholar database based on searches for the keyword